Volney Erskine Howard, The Statutes of the State of Mississippi 676 (1840) - (:unkn) unknown (My University, 1840)
§ 55 : If any person having or carrying any dirk, dirk knife, Bowie knife, sword, sword cane, or other deadly weapon, shall, in the presence of three or more persons, exhibit the same in a rude, angry and threatening manner, not in necessary self-defense, or shall in any manner unlawfully use the same in any fight or quarrel, the person or persons so offending, upon conviction thereof in the circuit or criminal court of the proper county, shall be fined in a sum not exceeding five hundred dollars, and be imprisoned not exceeding three months.
Keywords: BRANDISHING